Morphometric analysis of oculomotor triangle in dry human skulls and its clinical applications - B Ashwin Krishna; Karthik Ganesh Mohanraj (Wolters Kluwer Medknow Publications, 2022)
The oculomotor triangle is denoted as the "Triangle of Hakuba" or the "Hakuba's Triangle." This oculomotor triangle is a significant anatomical landmark. Oculomotor nerve, abducens nerve and part of the internal carotid artery (ICA) lie in this triangle. The determination of this analysis is to calculate the oculomotor triangle in dry processed skull bones of the south Indian population and its clinical significance. Fifty-one processed skulls of human origin were received from Anatomy Department, Basic Medical Sciences, Saveetha Dental College. Length from anterior-clinoid process (ACP) to posterior-clinoid process (PCP), length from PCP to APEX, and length from ACP to APEX were measured. Paired samples t-test was considered to analyze the values between the right triangle with the left triangle. From the measurements taken, the mean for the left side of the oculomotor triangle, ACP to PCP was 8.0591 ± 0.52 mm and the right side was 7.5482 ± 0.52 mm. The mean left side of the oculomotor triangle, measured from PCP to APEX was 6.73 ± 0.48 mm and the right side was 6.55 ± 0.72 mm. The mean of the left side of the oculomotor triangle, measured from ACP to APEX was 15.94 ± 0.682 mm and the right side was 16.21 ± 0.747 mm. Through this paired triangle of the cranial cavity, the horizontal section of ICA may be correlated with numerous vascular-related pathological considerations.